2011
DOI: 10.1242/jcs.087122
|View full text |Cite
|
Sign up to set email alerts
|

Von Hippel-Lindau gene product directs cytokinesis: a new tumor suppressor function

Abstract: One of the mechanisms of tumorigenesis is that the failure of cell division results in genetically unstable, multinucleated cells. Here we show that pVHL, a tumor suppressor protein that has been implicated in the pathogenesis of renal cell carcinoma (RCC), plays an important role in regulation of cytokinesis. We found that pVHL-deficient RCC 786-O cells were multinucleated and polyploid. Reintroduction of wild-type pVHL into these cells rescued the diploid cell population, whereas the mutant pVHL-K171G failed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 46 publications
1
7
0
Order By: Relevance
“…Remarkably, several cytokinesis genes/proteins have also been found to play roles in cancer pathogenesis [reviewed in Normand and King, 2010;Lacroix and Maddox, 2012]. Cytokinesis proteins are frequently upregulated in cancer cells or are encoded by genes that are deleted or amplified in human cancers [Roversi et al, 2006;Lind et al, 2011;Sinha et al, 2011]. Thus, clarification of the molecular pathways involved in cytokinesis may also aid cancer diagnosis and the design of therapeutic strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, several cytokinesis genes/proteins have also been found to play roles in cancer pathogenesis [reviewed in Normand and King, 2010;Lacroix and Maddox, 2012]. Cytokinesis proteins are frequently upregulated in cancer cells or are encoded by genes that are deleted or amplified in human cancers [Roversi et al, 2006;Lind et al, 2011;Sinha et al, 2011]. Thus, clarification of the molecular pathways involved in cytokinesis may also aid cancer diagnosis and the design of therapeutic strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Von Hippel–Lindau syndrome (VHL) is characterized by pheochromocytomas, renal agiomas, haemangioblastomas and renal cell carcinoma. The protein mutated in Von Hippel‐Lindau syndrome, pVHL, has recently been shown to be required for the recruitment of Alix and endobrevin to the midbody 105. These proteins interact with ESCRT‐1, which has been implicated in cytokinetic abscission 106, 107.…”
Section: Diseases Associated With Cytokinesis Failurementioning
confidence: 99%
“…These proteins interact with ESCRT‐1, which has been implicated in cytokinetic abscission 106, 107. Depletion of pVHL‐cell from retinal carcinoma cells caused chromosome instability and incomplete cytokinesis 105. Thus, the ploidy defects observed in VHL pathologies are likely due to misregulation of cytokinesis.…”
Section: Diseases Associated With Cytokinesis Failurementioning
confidence: 99%
“…Among these potential interacting proteins, Dynamin2 attracted our attention, for previous study showed that Dynamin2 might coordinate membrane remodeling and actin filament dynamics during cell morphogenesis and cell migration [18]. In addition, Dynamin2 has been localized to midbodies during cytokinesis [19]. The interaction between NTKL and Dynamin2 was further confirmed by co-immunoprecipitation assay (Figure 6E).…”
Section: Resultsmentioning
confidence: 69%